Features of media consumption by generation Z - Kasperovich-Rynkevich, Olga N. (Journal of the Belarusian State University. Journalism, 2019)
The significance of studying the preferences of representatives of generation Z for the media environment is justified. The structure of the younger generation of media consumption on the example of enrollees and students of the faculty of journalism of the Belarusian State University is analyzed. The main research method was a written survey, during which 148 respondents aged from 15 to 21 years old were interviewed. The author provides a detailed analysis of the results of the survey, on the basis of which the features of media consumption of the first representatives of the generation Z, as well as their personal characteristics were formed.